Measurement of the single top quark production cross section and vertical bar V-tb vertical bar in 1.96 TeV p(p)over-bar collisions with missing transverse energy and jets and final CDF combination - Aaltonen, T.; Amerioa, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
An updated measurement of the single top quark production cross section is presented using the full data set collected by the Collider Detector at Fermilab (CDF), corresponding to 9.5 fb(-1) of integrated luminosity from proton-antiproton collisions at 1.96 TeV center-of-mass energy. The events selected contain an imbalance in the total transverse momentum, jets identified as containing b quarks, and no identified leptons. The sum of the s- and t-channel single top quark cross sections is measured to be 3.53(-1.16)(+1.25) pb and a lower limit on the magnitude of the top-to-bottom quark coupling, vertical bar V-tb vertical bar of 0.63, is obtained at the 95% credibility level. These measurements are combined with previously reported CDF results obtained from events with an imbalance in total transverse momentum, jets identified as originating from b quarks, and one identified lepton. The combined cross section is measured to be 3.02(-0.48)(+0.49) pb and a lower limit on vertical bar V-tb vertical bar of 0.84 is obtained at the 95% credibility level.
Citation: Aaltonen, T., Amerioa, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Collaboration, C. D. F. (2016). Measurement of the single top quark production cross section and vertical bar V-tb vertical bar in 1.96 TeV p(p)over-bar collisions with missing transverse energy and jets and final CDF combination. Physical Review D, 93(3), 9. doi:10.1103/PhysRevD.93.032011
Additional Authors: Aurisano, A.;Azfar, F.;Badgett, W.;Bae, T.;Barbaro-Galtieri, A.;Barnes, V. E.;Barnett, B. A.;Barria, P.;Bartos, P.;Bauce, M.;Bedeschi, F.;Behari, S.;Bellettini, G.;Bellinger, J.;Benjamin, D.;Beretvas, A.;Bhatti, A.;Bland, K. R.;Blumenfeld, B.;Bocci, A.;Bodek, A.;Bortoletto, D.;Boudreau, J.;Boveia, A.;Brigliadori, L.;Bromberg, C.;Brucken, E.;Budagov, J.;Budd, H. S.;Burkett, K.;Busetto, G.;Bussey, P.;Butti, P.;Buzatu, A.;Calamba, A.;Camarda, S.;Campanelli, M.;Canelli, F.;Carls, B.;Carlsmith, D.;Carosi, R.;Carrillo, S.;Casal, B.;Casarsa, M.;Castro, A.;Catastini, P.;Cauz, D.;Cavaliere, V.;Cerri, A.;Cerrito, L.;Chen, Y. C.;Chertok, M.;Chiarelli, G.;Chlachidze, G.;Cho, K.;Chokheli, D.;Clark, A.;Clarke, C.;Convery, M. E.;Conway, J.;Corbo, M.;Cordelli, M.;Cox, C. A.;Cox, D. J.;Cremonesi, M.;Cruz, D.;Cuevas, J.;Culbertson, R.;d'Ascenzo, N.;Datta, M.;De Barbaro, P.;Demortier, L.;Deninno, M.;D'Errico, M.;Devoto, F.;Di Canto, A.;Di Ruzza, B.;Dittmann, J. R.;Donati, S.;D'Onofrio, M.;Dorigo, M.;Driutti, A.;Ebina, K.;Edgar, R.;Elagin, A.;Erbacher, R.;Errede, S.;Esham, B.;Farrington, S.;Ramos, J. P. F.;Field, R.;Flanagan, G.;Forrest, R.;Franklin, M.;Freeman, J. C.;Frisch, H.;Funakoshi, Y.;Galloni, C.;Garfinkel, A. F.;Garosi, P.;Gerberich, H.;Gerchtein, E.;Giagu, S.;Giakoumopoulou, V.;Gibson, K.;Ginsburg, C. M.;Giokaris, N.;Giromini, P.;Glagolev, V.;Glenzinski, D.;Gold, M.;Goldin, D.;Golossanov, A.;Gomez, G.;Gomez-Ceballos, G.;Goncharov, M.;Lopez, O. G.;Gorelov, I.;Goshaw, A. T.;Goulianos, K.;Gramellini, E.;Grosso-Pilcher, C.;Group, R. C.;da Costa, J. G.;Hahn, S. R.;Han, J. Y.;Happacher, F.;Hara, K.;Hare, M.;Harr, R. F.;Harrington-Taber, T.;Hatakeyama, K.;Hays, C.;Heinrich, J.;Herndon, M.;Hocker, A.;Hong, Z.;Hopkins, W.;Hou, S.;Hughes, R. E.;Husemann, U.;Hussein, M.;Huston, J.;Introzzi, G.;Iori, M.;Ivanov, A.;James, E.;Jang, D.;Jayatilaka, B.;Jeon, E. J.;Jindariani, S.;Jones, M.;Joo, K. K.;Jun, S. Y.;Junk, T. R.;Kambeitz, M.;Kamon, T.;Karchin, P. E.;Kasmi, A.;Kato, Y.;Ketchum, W.;Keung, J.;Kilminster, B.;Kim, D. H.;Kim, H. S.;Kim, J. E.;Kim, M. J.;Kim, S. H.;Kim, S. B.;Kim, Y. J.;Kim, Y. K.;Kimura, N.;Kirby, M.;Knoepfel, K.;Kondo, K.;Kong, D. J.;Konigsberg, J.;Kotwal, A. V.;Kreps, M.;Kroll, J.;Kruse, M.;Kuhr, T.;Kurata, M.;Laasanen, A. T.;Lammel, S.;Lancaster, M.;Lannon, K.;Latino, G.;Lee, H. S.;Lee, J. S.;Leo, S.;Leone, S.;Lewis, J. D.;Limosani, A.;Lipeles, E.;Lister, A.;Liu, H.;Liu, Q.;Liu, T.;Lockwitz, S.;Loginov, A.;Lucchesi, D.;Luca, A.;Lueck, J.;Lujan, P.;Lukens, P.;Lungu, G.;Lys, J.;Lysak, R.;Madrak, R.;Maestro, P.;Malik, S.;Manca, G.;Manousakis-Katsikakis, A.;Marchese, L.;Margaroli, F.;Marino, P.;Matera, K.;Mattson, M. E.;Mazzacane, A.;Mazzanti, P.;McNulty, R.;Mehta, A.;Mehtala, P.;Mesropian, C.;Miao, T.;Mietlicki, D.;Mitra, A.;Miyake, H.;Moed, S.;Moggi, N.;Moon, C. S.;Moore, R.;Morello, M. J.;Mukherjee, A.;Muller, T.;Murat, P.;Mussini, M.;Nachtman, J.;Nagai, Y.;Naganoma, J.;Nakano, I.;Napier, A.;Nett, J.;Neu, C.;Nigmanov, T.;Nodulman, L.;Noh, S. Y.;Norniella, O.;Oakes, L.;Oh, S. H.;Oh, Y. D.;Oksuzian, I.;Okusawa, T.;Orava, R.;Ortolan, L.;Pagliarone, C.;Palencia, E.;Palni, P.;Papadimitriou, V.;Parker, W.;Pauletta, G.;Paulini, M.;Paus, C.;Phillips, T. J.;Pianori, E.;Pilot, J.;Pitts, K.;Plager, C.;Pondrom, L.;Poprocki, S.;Potamianos, K.;Pranko, A.;Prokoshin, F.;Ptohos, F.;Punzi, G.;Fernandez, I. R.;Renton, P.;Rescigno, M.;Rimondi, F.;Ristori, L.;Robson, A.;Rodriguez, T.;Rolli, S.;Ronzani, M.;Roser, R.;Rosner, L.;Ruffini, F.;Ruiz, A.;Russ, J.;Rusu, V.;Sakumoto, W. K.;Sakurai, Y.;Santi, L.;Sato, K.;Saveliev, V.;Savoy-Navarro, A.;Schlabach, P.;Schmidt, E. E.;Schwarz, T.;Scodellaro, L.;Scuri, F.;Seidel, S.;Seiya, Y.;Semenov, A.;Sforza, F.;Shalhout, S. Z.;Shears, T.;Shepard, P. F.;Shimojima, M.;Shochet, M.;Shreyber-Tecker, I.;Simonenko, A.;Sliwa, K.;Smith, J. R.;Snider, F. D.;Song, H.;Sorin, V.;St Denis, R.;Stancari, M.;Stentz, D.;Strologas, J.;Sudo, Y.;Sukhanov, A.;Suslov, I.;Takemasa, K.;Takeuchi, Y.;Tang, J.;Tecchio, M.;Teng, P. K.;Thom, J.;Thomson, E.;Thukral, V.;Toback, D.;Tokar, S.;Tollefson, K.;Tomura, T.;Tonelli, D.;Torre, S.;Torretta, D.;Totaro, P.;Trovato, M.;Ukegawa, F.;Uozumi, S.;Vazquez, F.;Velev, G.;Vellidis, C.;Vernieri, C.;Vidal, M.;Vilar, R.;Vizan, J.;Vogel, M.;Volpi, G.;Wagner, P.;Wallny, R.;Wang, S. M.;Waters, D.;Wester, W. C.;Whiteson, D.;Wicklund, A. B.;Wilbur, S.;Williams, H. H.;Wilson, J. S.;Wilson, P.;Winer, B. L.;Wittich, P.;Wolbers, S.;Wolfe, H.;Wright, T.;Wu, X.;Wu, Z.;Yamamoto, K.;Yamato, D.;Yang, T.;Yang, U. K.;Yang, Y. C.;Yao, W. M.;Yeh, G. P.;Yi, K.;Yoh, J.;Yorita, K.;Yoshida, T.;Yu, G. B.;Yu, I.;Zanetti, A. M.;Zeng, Y.;Zhou, C.;Zucchellia, S.;Collaboration, C. D. F.
Keywords: Astronomy & Astrophysics; Physics